Conceptualisation de l’accompagnement des maitres de stage et analyse de ses effets chez les stagiaires - Charlotte Dejaegher; Fanny Watelet; Yves Depluvrez; Stéphanie Noël; Patricia Schillings (Activités)
This study is anchored in the field of professional didactics (Pastré, Mayen, & Vergnaud 2006). It aims, on the one hand, to analyze the operative model of two supervisors involved in the initial training of elementary school teachers and, on the other hand, to study the pre-service teachers’ perceptions of the benefits of the support provided. This study describes how two teachers take on this supervisory role in the context of French-speaking Belgian education, where neither the supervisory function nor the associated professional tasks are defined. The theoretical framework of the professional didactics, which is based on the reflexive stance that professionals adopt to revisit their activity, allowed me to highlight the conceptual elements that guide the activity of supervising. Moreover, through the observation of their activity during the debriefings with the trainees and through the analysis of what those supervisors said after the debriefing (using clarificatory interview techniques; Vermersch, 1994), a certain number of organizing concepts of their activity have been established. These results were then compared with the data collected from the trainees regarding the perceived benefits of the support received during their placement. The results reveal that the supervisors share concerns about the emotional and cognitive development of their trainee. However, these concerns translated into different postures of support. Furthermore, I identified some gaps between the way these professionals describe their activity and their actual activity.